The SlHB8 acts as a negative regulator in tapetum development and pollen wall formation in Tomato. Issue 1 (25th August 2022) - Wu, Caiyu; Yang, Yang; Su, Deding; Yu, Canye; Xian, Zhiqiang; Pan, Zanlin; Guan, Hongling; Hu, Guojian; Chen, Da; Li, Zhengguo; Chen, Riyuan; Hao, Yanwei
Abstract: Pollen development is crucial for the fruit setting process of tomatoes, but the underlying regulatory mechanism remains to be elucidated. Here, we report the isolation of one HD-Zip III family transcription factor, SlHB8, whose expression levels decreased as pollen development progressed. SlHB8 knockout using CRISPR/Cas9 increased pollen activity, subsequently inducing fruit setting, whereas overexpression displayed opposite phenotypes. Overexpression lines under control of the 35 s and p2A11 promoters revealed that SlHB8 reduced pollen activity by affecting early pollen development. Transmission electron microscopy and TUNEL analyses showed that SlHB8 accelerated tapetum degradation, leading to collapsed and infertile pollen without an intine and an abnormal exine. RNA-seq analysis of tomato anthers at the tetrad stage showed that SlHB8 positively regulates SPL/NZZ expression and the tapetum programmed cell death conserved genetic pathway DYT1–TDF1–AMS–MYB80 as well as other genes related to tapetum and pollen wall development. In addition, DNA affinity purification sequencing, electrophoretic mobility shift assay, yeast one-hybrid assay and dual-luciferase assay revealed SlHB8 directly activated the expression of genes related to pollen wall development. The study findings demonstrate that SlHB8 is involved in tapetum development and degradation and plays an important role in anther development.